Clinical application status and development of TNBC (BC) monoclonal antibody - Ding, Zian (Transactions on Materials, Biotechnology and Life Sciences, 2024)
A particular subtype of breast cancer known as triple-negative breast cancer (TNBC) is distinguished by the lack of ER, PR, and HER2 expression, culminating in HER2-targeted therapy with a poor prognosis and inadequate conventional hormone therapy. With the growing comprehension of the biological traits of TNBC in recent years, treatment strategies have gradually developed, particularly the use of mAb medications, which has renewed optimism for the treatment of TNBC. Because of its high specificity and targeting, mAb drugs have shown remarkable efficacy and potential in cancer treatment. An extensive examination of the clinical usage of mAb medications in the treatment of TNBC is given in this review. summarizing clinical trial data on key drugs such as PD-1/PD-L1 and TROP-2-targeted drugs, demonstrating the significant effect of these drugs in prolonging PFS and OS in patients. At the same time, new therapeutic targets besides PD-1 and TROP-2 are discussed, as well as the potential advantages of combination therapy strategies. The clinical application of mAb medications in TNBC is thoroughly examined in this study., summarizing clinical trial data on key drugs such as PD-1/PD-L1 and TROP-2-targeted drugs, demonstrating the significant effect of these drugs in prolonging PFS and OS in patients. At the same time, new therapeutic targets besides PD-1 and TROP-2 are discussed, as well as the potential advantages of combination therapy strategies.